Neonatal Effects of Magnesium Sulfate Given to the Mother - Abbassi-Ghanavati, Mina; Alexander, James M.; McIntire, Donald D.; Savani, Rashmin C.; Leveno, Kenneth J. (American Journal of Perinatology, 2012)
Objective Magnesium historically has been used for treatment and/or prevention of eclampsia or preterm labor. More recently, antepartum magnesium sulfate has been suggested for prevention of cerebral palsy in preterm infants. Although adverse effects and toxicity of magnesium in pregnant women are well known, the fetal-neonatal effects of magnesium are less clear. The objective of this study was to evaluate the effects of magnesium on the newborn infant.Study Design This is a retrospective cohort analysis of women who received antepartum magnesium sulfate for prevention or treatment of eclampsia. Magnesium sulfate was given intravenously beginning with a 6-g dose, followed by 2- to 3-g/h infusion. Newborn hypotonia was diagnosed if an infant exhibited less than normal tone/activity upon admission to the nursery.Results Between January 2000 and February 2009, a total of 6654 women with preeclampsia were treated with intravenous magnesium sulfate as described; 88 (6%) of the infants were diagnosed with hypotonia. Lower 1-minute and 5-minute Apgar scores, intubation in the delivery room, admission to special care nursery, and hypotonia were all significantly increased as maternal serum magnesium concentrations increased before birth.Conclusion Several neonatal complications are significantly related to increasing concentrations of magnesium in the maternal circulation.
Keywords: magnesium sulfate; neuroprotection; neonatal side effects; neonatal hypotonia; prevention of cerebral palsy